Why are wage shares worsening in a competitive economy? A brief review of pays equality and industrial politics - Maria Praptiningsih (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2022)
Wage shares have fallen substantially almost all over the world over the past 30 years. This study aims to provide a discussion of the critical elements of wage shares and to undertake a critical review of the empirical papers regarding the issue of the income distribution for labour. This paper investigates the wage share and determinants of 34 countries in 2011. There are two main objectives of this research. Firstly, the paper attempted to analyse the effectiveness of the incentives system, which is more likely to be rigid in the competitive work environment. Secondly, the research has emphasised how workers' behaviour can lead to different incentives payment through a kind of predatory behaviour or later on, we can call it an uncooperative behaviour. These objectives derived from the previous paper result in the adverse selection of worker turnover (Lazear, 1986). The findings confirm that the effect of globalisation through current account balance and the structural policy with tax wedge rate is statistically significant in wage share for those with low wage share (at the 10th per cent quantile) only. However, there is limited evidence that inflation, unemployment, education policy, and unionisation strongly affect the distribution of wages